Tingkat Partisipasi Masyarakat Dalam Mencegah Kebakaran Hutan dan Lahan di Kawasan Penyangga Suaka Margasatwa Giam Siak Kecil Kabupaten Bengkalis Provinsi Riau - Rinaldo, Rinaldo; Siregar, Yusni Ikhwan; Siregar, Sofyan Husein (Dinamika Lingkungan Indonesia, 2017)
The study was conducted from March to May 2016, in the buffer zone of Giam Siak Kecil Wildlife Reserve (SM GSK) Pinggir sub district of Bengkalis, Riau province. Purpose of the study Describe forest and land cover changes as well as hotspot spreads in the GSK SM buffer zone and describe the level of community participation in preventing forest and land fires in SM GSK buffer zones. The result is that the change of forest and land cover in the buffer zone of SM GSK in 2003-2015 occurred due to the opening of land for cultivation activities. The most significant changes occurred in the type of plantation land closure of 31.32% of the buffer area of SM GSK, followed by the swamp bush 15.29%, secondary forest of 10.87% and the plantation forest 9.40%. Data of fire point in sub-district in 2003 as many as 150 points, in 2009 as many as 161 points and 2015 only 31 points. The level of community participation in preventing the occurrence of forest and land fires in the buffer zone of SM GSK is influenced by high economic needs factor (60.16%), knowledge level (49.99%), social needs (59.09%) and implementation Regulations and law enforcement (54.09%) in the medium category. Overall factor of community participation level was in medium category (56,51%).